Correlation between F2-Isoprostane with stromal cell-derived factor-1 (SDF-1) and endothelial progenitor cell in nonhypertensive and hypertensive patients (Faculty of Medicine Universitas Indonesia, 2010)
Aim Circulating endothelial progenitor cells (EPCs) are reduced in number and function in patients at risk for cardiovascular diseases. On the other hand, hypertension is related with excess angiotensin II which would lead to oxidative stress. In this study, we investigated the correlation between F2-Isoprostane (as marker of oxidative stress) with Stromal Cell-Derived Factor-1 (SDF-1) and CD34 viable in non hypertension and hypertension subjects. Methods This was a cross sectional study conducted on 54 non hypertension and 64 hypertension subjects visiting Prodia laboratory, Jakarta. F2-Isoprostane (as marker of oxidative stress) and SDF-1 (a strmal cell growth factor) were measured by ELISA method, and CD34 viable (marker of progenitor cell) was measured by flow cytometry. Results F2-Isoprostane concentration was higher in hypertensive subjects compared to non hypertensive subjects, although statistically non significant (mean + SD: 0.13 ± 0.120 vs 0.10 ± 0.16; ρg/mL; p = 0.091). SDF-1 concentration was significantly higher in hypertensive subjects compare to non hypertensive subjects (2821.63 ± 281.94 vs 2623.04 ± 356.28 ρg/mL; P < 0.05). CD34 viable level was significantly lower in hypertensive subjects compare to non hypertensive subjects (1.9 ± 0.9 /μL vs 2.7 ± 1.7; P < 0.05). F2-Isoprostane had negative correlation with CD34 viable in circulation (r = 0.022, p < 0.05) but no correlation with SDF-1 (p > 0.05). Conclusions F2-Isoprostane was higher, but CD34 was lower, in hypertensive subjects compared to non hypertensive. It seems that high F2-Isoprostane impaired the CD34 viable level as shown by negative correlation between F2-Isoprostane and CD34. (Med J Indones 2010; 19:109-12)